The relevance of a Purpose-Driven Strategy in enabling FMCG companies to sustain long-term Customer loyalty and optimal Financial Performance : a South African perspective - Erasmus, Alet (University of Pretoria, 2023)
Mini Dissertation (MBA)--University of Pretoria, 2022.